IMPACT DE LA TAXE REMUNERATOIRE ANNUELLE SUR LA MAXIMISATION DES RECETTES NON FISCALES : Cas de la Province Orientale démembrée de janvier 2018 à décembre 2020 - LILEMBE, Godelieve OMONDO (IJRDO - Journal of Business Management, 2022)
At the end of this research entitled : Impact of the annual compensatory tax on the maximization of no-tax revenue generated by the DGRAD (case of the Eastern Province dismembered from January 2018 to December 2020, it is appropriate to bring to the attention of our readers that : During the thrée years selected for this research, the share of revenue generated by annual compensatory tax is too low ; The annual remunerative tax collected by the DGRAD in the Eastern Province dismembered from January 2018 to December 2020 has increased ; During the three years selected for this study, the revenue generated by the annual compensatory tax significantly influenced the no-tax revenue generated by the DGRAD in the Eastern Province dismembered.